The use of primary stenting or balloon percutaneous transluminal coronary angioplasty for the treatment of acutely occluded saphenous vein grafts. Results from the Brazilian National Registry - CENIC - Mattos,Luiz Alberto (2001)
OBJECTIVE: We conducted a comparative analysis of the in-hospital outcomes of patients who underwent primary percutaneous transluminal angioplasty (PTCA) or stent implantation because of an acute myocardial infarction (AMI) related to an acute vein graft occlusion. METHODS: Since 1991 the Brazilian Society of Hemodynamic and Interventional Cardiology has maintained a large database (CENIC). From these, we selected all consecutive patients, who underwent primary PTCA or stenting in the first 24 hours of AMI, with the target vessel being an occluded vein graft. Immediate results and major coronary events occurring up until hospital discharge were analyzed. RESULTS: During this period, 5,932 patients underwent primary PTCA or stenting; 158 (3%) of the procedures were performed because of an acute vein graft occlusion. Stenting was performed in 74 (47%) patients. Patients treated with stents had a higher success rate and lower mean residual stenosis compared with those who underwent primary balloon PTCA. The incidence of reinfarction and death were similar for stenting and balloon PTCA. CONCLUSION: Primary percutaneous treatment of AMI related to acute vein graft occlusion is still an uncommon practice. Primary stenting improved luminal diameter and offered higher rates of success; however, this strategy did not reduce the in-hospital reinfarction and death rate, compared with that occurring with PTCA treatment.